2006
DOI: 10.1890/0012-9658(2006)87[2614:vposdm]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Variation Partitioning of Species Data Matrices: Estimation and Comparison of Fractions

Abstract: Establishing relationships between species distributions and environmental characteristics is a major goal in the search for forces driving species distributions. Canonical ordinations such as redundancy analysis and canonical correspondence analysis are invaluable tools for modeling communities through environmental predictors. They provide the means for conducting direct explanatory analysis in which the association among species can be studied according to their common and unique relationships with the envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
1,539
0
15

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,970 publications
(1,600 citation statements)
references
References 39 publications
5
1,539
0
15
Order By: Relevance
“…This was consistent with the finding that soil conductivity was one of the most important factors in structuring plant communities (Peres-Neto et al 2006;Corriale, Picca, and Francescantonio 2013) and that A. donax, growing in Community I, tended to occur on clay soils. Only certain species, such as Z. latifolia and T. orientalis, were able to grow in Community III, and A-P was important in structuring this community; A-P was usually an important factor for vegetation development and distribution in wetlands and therefore it was significant in vegetation restoration in such areas (Ladányi et al 2016).…”
Section: Relationship Between Vegetation and Soil Factorssupporting
confidence: 91%
See 2 more Smart Citations
“…This was consistent with the finding that soil conductivity was one of the most important factors in structuring plant communities (Peres-Neto et al 2006;Corriale, Picca, and Francescantonio 2013) and that A. donax, growing in Community I, tended to occur on clay soils. Only certain species, such as Z. latifolia and T. orientalis, were able to grow in Community III, and A-P was important in structuring this community; A-P was usually an important factor for vegetation development and distribution in wetlands and therefore it was significant in vegetation restoration in such areas (Ladányi et al 2016).…”
Section: Relationship Between Vegetation and Soil Factorssupporting
confidence: 91%
“…Quantifying the variation in species diversity and community composition with location provided the opportunity to infer possible mechanisms of vegetation community assembly (Kadowaki et al 2014;Reid, Reid, and Thoms 2016;Yamaji et al 2016). Similar results were found in lowlands, temperate forests, arid grasslands, beech forests, and natural forest (Peres-Neto et al 2006;Dwirek, Kauffman, and Baham 2006). We found that the main factors affecting vegetation distribution were SOM, Cond, pH, TP, and A-P. SOM provides nutrients to plants, ensures plant production and development, and plays an important role in the sustainable development of the wetland.…”
Section: Relationship Between Vegetation and Soil Factorsmentioning
confidence: 62%
See 1 more Smart Citation
“…We further quantified the influences of environmental variables (pH+DO+NO x +POC+CH 4 +Chl-a), depth, and season on bacterial community variation using variation partitioning analyses [46], with the varpart function of the vegan package [47,36]. If any colinearity was present, it would be revealed by the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…To investigate which soil attributes best explained the variability in ARISA profiles, a Non-metric multidimensional scaling (NMDS) was performed in Canoco 4.5 (Biometrics, Wageningen) with Hellinger transformed data [15]. This multivariate analysis was supplemented with environmental data.…”
Section: Arisa Data Analysismentioning
confidence: 99%